2020
DOI: 10.1007/s40472-020-00308-9
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Wall Transplantation: Indications and Outcomes

Abstract: Purpose of Review This article aims to review published outcomes associated with full-thickness vascularized abdominal wall transplantation, with particular emphasis on advances in the field in the last 3 years. Recent Findings Forty-six full-thickness vascularized abdominal wall transplants have been performed in 44 patients worldwide. Approximately 35% of abdominal wall transplant recipients will experience at least one episode of acute rejection in the first year after transplant, compared with rejection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…However, in the 14 cases reported by Miami and Bologna, ACRs of AW‐VCA and ITx did not occur together and were always discordant 3 ; accordingly, the utility of AW‐VCA skin as an immune monitor for ITx needs to be assessed and verified 4 . However, it may be unethical to observe skin rejection and withhold immunosuppressants to see whether the intestine will subsequently undergo cellular rejection, 3 so comparing AW‐VCA skin and ITx mucosa rejections should rely on animal models.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, in the 14 cases reported by Miami and Bologna, ACRs of AW‐VCA and ITx did not occur together and were always discordant 3 ; accordingly, the utility of AW‐VCA skin as an immune monitor for ITx needs to be assessed and verified 4 . However, it may be unethical to observe skin rejection and withhold immunosuppressants to see whether the intestine will subsequently undergo cellular rejection, 3 so comparing AW‐VCA skin and ITx mucosa rejections should rely on animal models.…”
Section: Introductionmentioning
confidence: 85%
“…Abdominal wall‐vascularized composite allotransplantation (AW‐VCA) was successfully proposed in 2001 to provide abdominal coverage for patients after ITx 2 . Over the past two decades, 46 AW‐VCAs have been performed in 44 patients across seven international medical centers worldwide 3 . Moreover, AW‐VCA skin can facilitate early detection of acute cellular rejection (ACR) of ITx since Gerlach et al from Oxford reported no cases of ITx mucosa ACR without preceding or simultaneous AW‐VCA skin ACR 2,3 …”
Section: Introductionmentioning
confidence: 99%
“…The potential advantage would be the preservation of the donor iliac vessels for the vascular toolkit. Overall, a recent collection of the worldwide experience has reported 46 AWT transplants performed in 44 patients [20 ▪▪ ,21–23] (see Table 1). The reported 1- and 3-year intestinal graft survival rates were 94% and 57%, respectively in this cohort.…”
Section: Full-thickness Abdominal Wall Transplantationmentioning
confidence: 99%
“…AWT, abdominal wall transplant; GvHD, graft versus host disease; PTLD, posttransplant lymphoproliferative disease.Adapted from Honeyman et al [20 ▪▪ ].…”
Section: Full-thickness Abdominal Wall Transplantationmentioning
confidence: 99%
See 1 more Smart Citation